Determinants of proportions of household land used for forestry practice in Southeast Nigeria (2017)
Forestry activities if properly planned, designed and executed can provide significant economic, social and environmental benefits. But land availability and more importantly size, determines the level of investment in forestry. The growing scarcity and social issues surrounding land acquisition necessitate identifying opportunities to enhance forestry development at the household level. Thus, this study investigated the determinants of the proportion of a household land that can be put into forestry use by households in South-eastern Nigeria. Seven (7) communities were randomly selected from Imo and Anambra States. Semi-structured questionnaire was administered to ten percent (10%) of heads of households in the selected communities. A total of 547 sets of questionnaire were administered but, 490 were used for analysis. The questionnaire was based on the socio-economic background of the respondents, their number of farmlands, average size of farmland unit and proportion of the household farmlands, which can be used for forestry activity. Data generated were analysed using bar chart, frequency table and Tobit regression. Modal percentage of total farm land available for forestry activities was 54.0% while the lowest was 17.4%. Also, the form of household leadership, occupation and education of respondents as well as indigenous forestry groups had impacts on the percentage of land area that household heads are putting up for forestry activities in the study area. While male headed households and farmers show more interest in forestry activities, the educated elites hold a reverse perception.